Global commons and the law of the sea - Zou, Keyuan (Maritime cooperation in East Asia, 2018)
Global Commons' refers to resource domains or areas that lie outside of the political reach of any one State, including sea areas beyond national jurisdiction and Antarctica. The concept of 'global commons' is a living concept and can accommodate, over time, other commons at the international level, such as biodiversity and generic resources. The situation of global marine commons is not that optimistic in that fishery resources continue to deplete, marine biodiversity continue to reduce, and plastic wastes in the oceans continue to increase. In international law, there are legal regimes governing global marine commons. A most important global treaty is the 1982 United Nations Convention on the Law of the Sea (LOSC), which came into effect in 1994. It governs the high seas, international seabed and its resources, marine environmental protection, and fisheries.0'Global Commons and the Law of the Sea' offers intellectual discussions on global marine commons. It contains six parts respectively addressing the principle of the common heritage of mankind (CHM), freedoms of high seas, deep sea mining and international seabed, area beyond national jurisdiction (ABNJ) governance, management of geoengineering and generic resources, and recent developments in the polar regions.